The Use of judgement heuristics to make social and object decisions a developmental perspective - Jacobs, Janis E.; Potenza, Maria ([Place of publication not identified] Blackwell Publishing, 1991)
This study examined the developments of children's use of 2 judgement strategies: (1) the use of base rates and (2) the use of the respectiveness heuristic. Children in the first (M= 6.85), third (M= 8.86), and sixth grades (M= 11.27) and a comparison sample of college students (M= 20.11) made judgements about scenarios that varied by domain (social vs. object judgements) and by information provided (base rates only vs. base rates and individuating information). Results indicated that although the use of base rates and the representativeness heuristic increased with age, the use of individuating information to make social judgements developed quite early. Consistency between subjects' choices and rationales increased significantly with grade level, indicating that younger children use idiosyncratic strategies, such as personal preferences or scenario embellishment, to make decisions. Developmental trends are discussed in light of previous research with adults.
Includes bibiographical references.
Keywords: Heuristic